Pengaruh Kinerja Perusahaan terhadap Penghindaran Pajak dengan Ukuran Perusahaan sebagai Variabel Moderasi - Shinta Nuriyah Fajrin; Rediyanto Putra (Universitas 45 Surabaya, 2025)
This study aims to determine the effect of profitability, leverage, and sales growth on tax avoidance with firm size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The study uses secondary data obtained from annual financial reports of the companies. The sampling technique employed is purposive sampling, with a total of 65 companies meeting the research criteria. Data analysis was conducted using moderated multiple linear regression with the help of SPSS version 26. The results show that profitability, leverage, sales growth, and firm size each have a significant effect on tax avoidance. Furthermore, firm size moderates the relationship between the independent variables and tax avoidance. Specifically, firm size weakens the influence of profitability and leverage on tax avoidance but strengthens the influence of sales growth on tax avoidance. These findings indicate that firm size plays an important role in shaping the tax management strategies adopted by companies. This research is expected to provide insights for companies, investors, and policymakers in understanding the factors affecting tax avoidance practices and to encourage greater transparency and tax compliance within the manufacturing sector.